The Relationship of Father's Role to Stunting Prevention: Study Literature - Antasari, Dwi; Alam Fajar, Nur; Flora, Rostika (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Since it affects almost every region of the world, the problem of nutrition is considered a global health problem. A child's growth and development can be slowed down by malnutrition. A serious nutritional problem in Indonesia is the increasing problem of malnutrition in toddlers and school-aged children. children. As caregivers, educators, supervisors, disciplinarians, protectors, and supporters who have a significant impact on stunting prevention in toddlers, including the role of fathers in stunting prevention is very important. Even if the culture does not comply with child health recommendations, all recommendations must be followed because parents are assumed to have more experience in caring for children. Stability can be avoided with good parenting. All children's needs will be met if they are cared for properly, and children will grow and develop optimally.